En el contexto de Alberdi y la guerra del Paraguay: Estado, capitalismo y sociedad en los conflictos del Cono Sur, 1860-1880. - Eduardo Cavieres F. (Centre de Recherches sur les Mondes Américains, 2009)
Rather than looking into the political or military analysis of the conflict, this study is a reflection about the contexts in which the Pacific, and specifically the Paraguayan, wars happened. In addition, the aim is to consider how the internal problems of each country – which together constituted the problems of the region- not only were not resolved through the armed conflicts, but in many ways made manifest the evident contradictions that existed between the path towards liberal modernity and the countries’ social underdevelopment. This work also points out that during this time period, the need for a Latin American Union was already a wish detached from reality. Most of the contents of the work is based on Juan Bautista Alberdi.